Effect of different citrus sweets on the development of enamel erosion in vitro - Beatriz Martines de SOUZA; Mariele VERTUAN; Isabela Vieira Bolzan GONÇALVES; Ana Carolina MAGALHÃES (University of São Paulo, 2020)
Abstract The increased consumption of citrus sweets can contribute to the development of erosive tooth wear (ETW). Objective This in vitro study evaluated the erosive potential of citrus sweets on bovine enamel samples regarding the quantification of wear. Methodology Ninety bovine crowns were prepared and samples were randomly distributed into 6 groups (n=15): 0.1% citric acid solution (pH 2.5); Coca-Cola ® Soft Drink (pH 2.6); Fini ® Diet (lactic and citric acid, pH 3.3); Fini ® Jelly Kisses (lactic and citric acid, pH 3.5); Fini ® Fruit Salad Bubblegum (maleic acid, pH 2.6); Fini ® Regaliz Acid Tubes (maleic and citric acid, pH 3.1). Sweets were dissolved in the proportion of 40 g/250 mL of deionized water. Enamel samples were submitted to erosive challenges for 7 days (4 daily acid immersion cycles for 90 s each). Enamel wear was measured using contact profilometry (μm), and data (median values [interquartile range]) were submitted to Kruskal-Wallis/Dunn's test (p<0.0001). Results All citrus sweets tested present a high erosive potential, Fini Diet ® (2.4 [1.2]) and Fini Regaliz Tubs ® (2.2 [0.5]) show the highest erosive potential, similar to 0.1% citric acid (2.3 [0.7]); Fini Regaliz Tubs ® is more erosive than Coca-Cola ® (1.4 [0.9]). Conclusion The evaluated citrus sweets have great erosive potential and play a key role in the development of ETW.